Anaerobic Digestion Of Mixed Chemical Pulping And Palm Oil Mill Effluent In Suspended Growth Anaerobic Digester. - Ismail, Norli; Ho, Chew Meng; Ling, Y.L. (2006)
The feasibility of anaerobic digestion treating palm oil mill effluent (POME) with addition of chemical pulping wastewater (black liquor) was studied in semi-continuous fed digesters under thermophilic (55°C) condition. The anaerobic digestibility of POME with and without addition of black liquor (2.5% and 5% by volume) was compared. Black liquor is an effluent obtained from pulping processes and it has high toxicity level and poor biodegradability. The digesters contained POME without black liquor functioned as a control in this study. The chemical oxygen demand (COD) reduction for hydraulic retention time (HRT) of 5 days and 10 days were examined to evaluate the effect of HRT on the performance of the digesters. The results depicted that COD reduction could be achieved up to 87% in the digester without black liquor and 79% reduction in COD with black liquor added. Fourier Transform Infrared (FTIR) spectroscopy was used to identify the functional group of POME operated under thermophilic temperatures and with or without addition of black liquor. Differences in the functional group were depicted within ten days HRT for both conditions. The results of this work could be used as a basis to enhance the possibility of anaerobic digestion in treating the chemical pulping wastewater which is initially known difficult to degrade biologically.